Supercritical water technology: an emerging treatment process for contaminated wastewaters and sludge - de Souza, Guilherme Botelho Meireles [UNESP]; Pereira, Mariana Bisinotto; Mourão, Lucas Clementino; dos Santos, Mirian Paula [UNESP]; de Oliveira, José Augusto [UNESP]; Garde, Ivan Aritz Aldaya [UNESP]; Alonso, Christian Gonçalves; Jegatheesan, Veeriah; Cardozo-Filho, Lúcio [UNESP] (Springer Nature, 2022)
The destruction of toxic, persistent, refractory, and hazardous organic compounds, often present at high concentrations in both industrial and municipal wastewaters, remains a major challenge to be overcome, mainly due to the inefficiencies of conventional processes. Notwithstanding, the search for novel treatment methods has received great attention recently. Supercritical water technology has proved to be a very promising treatment method for contaminated wastewaters and sludges. Performances of supercritical water technology in treating wastewaters from a wide variety of industries including pulp and paper, pharmaceutical, textile, pesticides, dairy, petrochemical, explosives, and distillery were reviewed. Furthermore, the effects of main operating conditions, namely temperature, pressure, residence time on the treatment efficiency, usually reported in terms of total organic carbon and chemical oxygen demand removal were summarized. In addition, well-known technical challenges faced by supercritical water processes such as corrosion, salt deposition, clogging, elevated running costs and possible solutions to mitigate those challenges have been discussed. At last, the future scope of the supercritical water technology is expected to be driven by policies aiming at the reduction of greenhouse gas emissions, environmental protection, mitigation of climate changes and the production of commercial gases from highly efficient treatment of contaminated organic wastewaters and sludges.
Keywords: Contaminated sludge; Industrial wastewater; Persistent pollutants; Supercritical water; TOC removal